Perancangan dan Pembuatan Aplikasi Sistem Kontrol Absensi Dosen Politeknik Negeri Kupang Studi Kasus Pada Jurusan Teknik Elektro - Jemsrado Sine; Daniel S Bataona; Rivaldo I Nessi (Pusat Riset dan Inovasi Nasional, 2024)
It is undeniable that the presence of lecturers in the implementation of learning activities in the classroom is still very much needed by students, especially for learning that requires communication between lecturers and students. As in the learning process in the Electrical Engineering Department, Kupang State Polytechnic. To ensure the presence of lecturers during lectures, a system is needed that can ensure that lecturers have actually been present in class for scheduled lectures. So to overcome these obstacles, a real-time lecturer attendance information system application is needed during lectures. The system overview is that lecturers can take attendance if they have entered the class for the scheduled time at that time. Furthermore, the lecturer will provide validation as a form of confirmation that the lecturer of the course at that time is really present on a web-based basis. The results can help attendance more efficiently in handling student and lecturer attendance. In addition, this attendance system application presents attendance information to the lecturer, lecturer, admin, and head of study program online. This study aims to design and build a website-based lecturer attendance application, with the research method used being the waterfall method with stages that will be passed by the author including analysis, design, coding, and testing.